A Case Study Approach to Families Risk of Hyperemesis Gravidarum: Community Midwifery Care - Sumaifa Sumaifa; Isnaeny Isnaeny; Rahmi Suci Ramadhani (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Hyperemesis gravidarum (HG) is a pregnancy complication characterized by excessive nausea and vomiting, which may lead to dehydration, electrolyte imbalance, weight loss, and adverse health problems for both mother and fetus. Effective management of HG requires not only clinical intervention but also comprehensive family support and community-based midwifery care. This case study describes the application of community midwifery care for families at risk of HG and identifies family-related factors influencing the success of case management. A qualitative exploratory case study approach was employed to examine family perspectives on health services in depth, focusing comprehensively on a single case. Informants were selected purposively, with inclusion criteria targeting pregnant women at risk of HG. Data were collected through observation, interviews, physical examinations, and home visits. The findings revealed that the pregnant woman, Mrs. R, experienced severe nausea and vomiting, which reduced her appetite and daily functioning. Risk factors included her fourth pregnancy and limited family support, especially from her husband. Community midwifery interventions comprised education about HG, nutritional counseling, maternal condition monitoring, and family involvement in her care. Following these interventions, the mother's condition improved, as evidenced by reduced nausea and vomiting and enhanced family capacity to support her pregnancy. In conclusion, family-centered community midwifery care plays a crucial role in managing hyperemesis gravidarum. Ongoing education and family involvement can mitigate complications and promote maternal and fetal health during pregnancy Keyword: Case Study, Midwifery Care, Community, Hyperemesis Gravidarum